Croup - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Children do suffer from different diseases, some are common in small age group and some are common in all age group during pediatric age group. It is true for Nepal too. Among different diseases, croup is one of them.The viruses infect the nose and throat initially, and then spread along the upper respiratory tract (back of the throat) to the larynx and trachea .As the infection progresses, the top part of the trachea becomes swollen, which narrows the space available for air to enter the lungs. This leads to the symptoms of croup.Most children develop a fever, which may range from mild (100.4ºF or 38ºC) to very high (104ºF or 40.5ºC). The fever itself does not cause them harm, Croup may have symptoms such as rash, eye redness (called conjunctivitis), and swollen lymph nodes may develop, depending upon the virus causing the illness. Baby may present with dehydration if cannot drink well.